Taking Over Consumptive Loans Without Collateral: (Research Study on Bank Syariah Mandiri Lhokseumawe) - Faisal, Faisal; Maulana, Riki; Sulaiman, Sulaiman; Kunarti, Siti (Jurnal Dinamika Hukum, 2023)
The title of this research is taking over consumptive loans without collateral; (research study on Bank Syariah Mandiri Lhokseumawe). The approach method used is a qualitative descriptive approach. The results of the study, the implementation of the takeover of Multipurpose Micro credit of Bank Mandiri to Multipurpose financing of Bank Syariah Mandiri (BSM) by using a murabahah financing contract carried out by BSM Lhokseumawe Branch did not meet the pillars and contract requirements stipulated in the Sharia Economic Law Compilation. In the credit conversion process, it prioritizes the benefit aspect, namely leaving the disadvantages of the interest-based banking system towards the benefit of financing in Islamic banks in accordance with sharia principles. Expecting the importance of fulfilling sharia principles in the process of taking over credit without collateral from conventional banking into sharia banking products, the DSN-MUI needs to issue a fatwa to regulate the conversion of credit without collateral from conventional banking into sharia banking products.Keywords: consumer credit; financing; Islamic law, murabahah; sharia financial institution qanun.